Knowledge Management in Local Public Health: Gaps and Opportunities in Rural Municipalities; [Gestión del Conocimiento en Salud Pública Local: Brechas y Oportunidades en Municipios Rurales] - Perez-Arrau, J (Universidad del Zulia, 2025)
Knowledge management is key to strengthening public health, especially in municipalities with limited infrastructure and resources. The objective of this study is to understand the dynamics of knowledge management in the municipality of La Cumbre, Colombia, and its contribution to health promotion and equity. This study uses semi-structured interviews with health sector stakeholders and a literature review of Latin American initiatives related to knowledge management in health. The findings reveal progress in training processes and intersectoral partnerships, as well as limitations in knowledge systematization, strategy sustainability, and technological infrastructure. Community learning practices and social appropriation of knowledge were identified, although with limited impact assessment. It is concluded that strengthening knowledge management in health requires consolidating collaborative networks, integrating digital technologies, and ensuring the institutional continuity of strategies, thus promoting more informed and contextualized decision-making. © 2025, Universidad del Zulia. All rights reserved.
Keywords: information management; knowledge management; knowledge transfer; municipal government; public health